Suicide prevention skills training in pre-clerkship medical students: a pilot study - Zeeman, Michael; Chow, Jessica; Goldstein, Cheryl; Lewis, Melanie (Canadian Medical Education Journal, 2024)
When equipped with the skills to recognize and intervene effectively, peers are well positioned to be early responders to near-peers in mental distress. This pilot study provides a framework for providing suicide prevention skills training to pre-clerkship medical students with the aim to improve early peer-to-peer detection and initial aid for mental health crises. This training is effective in improving students’ self-reported comfort to provide early intervention to peers with declining mental health. Participants felt strongly that this training merits integration into core medical education and did not identify the added courseload as a major burden. Other programs should consider adopting such an initiative.